2023
DOI: 10.1111/2041-210x.14124
|View full text |Cite
|
Sign up to set email alerts
|

SWAMP: A new experiment for simulating permafrost warming and active layer deepening on the Tibetan Plateau

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Previous studies suggested that soil carbon emissions in grasslands had the highest uncertainty among all biomes 35 , 36 . In addition, Tibetan alpine grassland ecosystems, with huge carbon stocks 8 (7.4 Pg C in the top 1 m), may lose a large share of soil carbon with warming because warming increases thaw depth and duration 37 , and the effect size may be contingent on the size of initial soil C stock (based on surface or shallow soil warming experiments 38 ). But, thus far shallow warming experiments in alpine grassland ecosystems have not altered soil organic carbon stocks 20 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that soil carbon emissions in grasslands had the highest uncertainty among all biomes 35 , 36 . In addition, Tibetan alpine grassland ecosystems, with huge carbon stocks 8 (7.4 Pg C in the top 1 m), may lose a large share of soil carbon with warming because warming increases thaw depth and duration 37 , and the effect size may be contingent on the size of initial soil C stock (based on surface or shallow soil warming experiments 38 ). But, thus far shallow warming experiments in alpine grassland ecosystems have not altered soil organic carbon stocks 20 , 39 .…”
Section: Discussionmentioning
confidence: 99%